Antioxidant activity and physical-chemical properties of spray and spouted bed dried extracts of Bauhinia forficata - Claudia Regina Fernandes Souza; Sandra Regina Georgetti; Marcos José Salvador; Maria José Vieira Fonseca; Wanderley Pereira Oliveira (Universidade de São Paulo, 2009)
Two distinct drying methods (spouted bed and spray drying) were used for production of dried extracts of Bauhinia forficata Link (Leguminosae, Caesalpinoideae). High-quality powder products in terms of physical and chemical properties were obtained. HPLC fingerprints revealed that the chromatographic profiles of flavonoid compounds present in the dried extract did not change significantly, due to drying. In general, the spouted bed drying caused a degradation of total flavonoids than was lower than that of the spray drying. Antioxidant properties of the dried extract, examined by their radical scavenging activity using 2,2-diphenyl-1-picrylhydrazyl radical (DPPH•) and inhibition of lipid peroxidation induced by Fe+2 assays (LPO), confirmed their antioxidant potential. The slight reduction in scavenging activity of the dried extracts may be associated with the occurrence of oxidative reactions, decomposition or losses of thermolabile compounds, induced by the heat. Neste trabalho foram utilizados dois distintos secadores (leito de jorro e spray dryer) para a produção de extratos secos de Bauhinia forficata Link (Leguminosae, Caesalpinoideae) obtendo-se um produto seco com elevada qualidade em termos de suas propriedades físicas e químicas. Análises qualitativas obtidas por CLAE revelam que os perfis cromatográficos dos compostos flavonóides presentes nos extratos secos não apresentaram significativas mudanças durante a secagem quando comparados aos perfis obtidos para os extratos concentrados. Em geral, a secagem por leito de jorro acarreta menores perdas dos flavonóides totais do que a secagem em spray drying. A atividade antioxidante dos extratos secos foi examinada pelos métodos de (DPPH•) e peroxidação lipídica induzida por Fe+2 (LPO). Uma pequena redução na atividade sequestradora de radicais livres observada para os extratos secos pode ser associada com a ocorrência de reações oxidativas, decomposição e/ou perdas de compostos termolábeis induzidas pelo calor.